PARADYGMAT JAKO PODSTAWA NORMALNEGO UPRAWIANIA NAUKI: NAUKI SPOŁECZNE A PRZYRODOZNAWSTWO. UJĘCIE THOMASA SAMUELA KUHNA - Jankowski, Krzysztof (In Gremium. Studies in History, Culture and Politics, 2017)
Article aims to present how Kuhn behold the fundamental difference between the social sciences (especially sociology) and mathematical natural science (mainly physics, astronomy and chemistry) as well as to the issue they treated representatives of the social sciences. The first two parts represent the Kuhn’s understanding of paradigm and practicing normal science. In the third part of Kuhn’s insights about the nature of social theory compare with what think about this social scientists. Mostly sociologists are unanimous about the fact that pluralism theory of general testifies to the crisis in their discipline. Therefore they agree with what he thought about this Kuhn. In the environment, there are also different opinions. They show that, as in the natural sciences among themselves scholars there is no consensus as to which model of doing science – or pluralistic monottheoretical – is a model more desirable.